Synergistic effect between sulfate-reducing bacteria and Shewanella algae on corrosion behavior of 321 stainless steel - Ting Zhao; Lijun He; Zhenghui Qiu; Zhaoqi Zhang; Cunguo Lin (Journal of Materials Research and Technology, 2023)
Microbiologically influenced corrosion (MIC) caused by mixed microorganisms limits the application of 321 stainless steel (SS) in the field of ocean engineering. Therefore, in this paper, the synergistic effect of sulfate-reducing bacteria (SRB) and Shewanella algae (S. algae) on the corrosion behavior of 321 SS was studied by surface analysis and electrochemical measurements. The results revealed that riboflavin secreted by S. algae promoted the electron transfer between SRB and 321 SS by obtaining the electrons generated by the dissolution of metallic iron on the surface of SS and then transferring them to SRB, thus accelerating the MIC of 321 SS. Meanwhile, SRB gained electrons and reacted with SO42− to form HS−, which reacted with iron oxides in the Cr-rich passive film on the surface of SS to generate iron sulfides, providing thermodynamic and kinetic conditions for the formation of Cr6+. The formation of thermodynamically unstable Cr6+ destructed the passive film on the SS surface and promoted the development of pitting corrosion. The outcome provided a new perspective for studying the corrosion mechanism of extracellular electron transfer (EET)-MIC.